Construction Project Management : Theory and Practice. - Jha, Kumar Neeraj (2011)
Construction Project Management deals with different facets of construction management emphasizing the basic concepts that any engineering student is supposed to know. The major principles of project management have been derived through real life case studies from the field. Simplified examples have been used to facilitate better understanding of the concepts before going into the large and complex problems. The book features computer applications (Primavera and MS Project) used to explain planning, scheduling, resource leveling, monitoring and reporting; it is highly illustrated with line diagrams, cash-flow diagrams, bar diagrams, line graphs to make the book interactive and easy to understand; the pedagogy includes solved examples, and chapter-end exercises comprising both descriptive and non-descriptive questions; real life examples from sites of Delhi Metro construction, Delhi International Airport construction and many more; and case studies on preparation of documents for ISO 9001:2000, construction disputes, accidents in the construction industry, and preparation of estimates for live projects.
10.8 Profit and Loss Account.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2018. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books